Professional Competence Understanding Level of Elementary School in Implementing Curriculum 2013 - Wachidi Wachidi; Adrian Rodgers; Dmitriy Yu Tumanov (Universitas Bengkulu, 2020)
The specific purpose of this study is to find out professional competence understanding level of elementary school teacher in implementing curriculum 2013 in Bengkulu city. This study used analytical descriptive. This study aimed at describing the professional competence understanding level of elementary school teacher in implementing curriculum 2013. The subject of this study was 100 teachers of elementary schools in Bengkulu City. The object of this study was related to professional competence understanding level of elementary school teacher in implementing Curriculum 2013. The data collecting was conducted by using questionnaire and document. Questionnaire was used to obtain the data about professional competence understanding level of elementary school teacher in implementing Curriculum 2013. To find out and to proof that questionnaire is valid was conducted by expert. Document was used to find out the number of elementary school teacher in Bengkulu City. After the data was collected it was verified, and was processed by using percentage statistic method. The data processing was then analyzed and concluded. In general this study concluded that elementary school teachers in Bengkulu city understands professional competence in implementing curriculum 2013.